Atlas of pediatric cardiac CTA : congenital heart disease - Richardson, Randy Ray (Springer New York, 2013)
Atlas of Pediatric Cardiac CTA is a concise visual guide to the imaging of congenital heart disease in infants and children.  The book focuses on the utilization of cardiac CTA imaging for pediatric patients as distinct from adult patients, with an emphasis on techniques for retrospective and prospective scanning, reduction of the radiation dose, and CT data processing and analysis.  It also describes cardiac CTA evaluation search patterns to assess the complex anatomy in congenital heart patients.  As pediatric patients often present with multiple findings, separate chapters are devoted to the major structures of the cardiovascular system, accompanied with extensive imaging examples of the atria, ventricles, great vessels, coronary arteries, lungs and airways, and the situs. The book concludes with a review of shunts, procedures, and surgeries used in the management of these congenital disorders.  Atlas of Pediatric Cardiac CTA is a valuable resource for radiologists, cardiologists, and other clinicians or physicians in training involved in the care of pediatric patients with congenital heart disease.